Book Review of The Nile River Basin: Water, Agriculture, Governance and Livelihoods - Masson, Éric (International Journal of Water Governance, 2014)
by Seleshi Bekele Awulachew, Vladimir Smakhtin, David Molden and Don Peden (editors): Routledge (ed.), 2012, 344 pages, ASIN: B00GDF76P8.